The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0100936
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative De Novo Analysis of Full Length cDNA and Quantitative Analysis of Gene Expression for Common Marmoset (Callithrix jacchus) Transcriptomes Using Parallel Long-Read Technology and Short-Read Sequencing

Abstract: The common marmoset (Callithrix jacchus) is a non-human primate that could prove useful as human pharmacokinetic and biomedical research models. The cytochromes P450 (P450s) are a superfamily of enzymes that have critical roles in drug metabolism and disposition via monooxygenation of a broad range of xenobiotics; however, information on some marmoset P450s is currently limited. Therefore, identification and quantitative analysis of tissue-specific mRNA transcripts, including those of P450s and flavin-containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 58 publications
(62 reference statements)
2
20
0
Order By: Relevance
“…In a previous study, de novo gene expression analysis in marmosets indicated expression of the marmoset P450 4F11-like gene in the liver and the 4F12-like gene in the liver, small intestine, and kidney (Shimizu et al, 2014): however, marmoset P450 4F forms have not been identified and characterized. In this study, we identified four novel P450 4F genes using the marmoset genome data, including P450 4F2, 4F3, 4F11, and 4F12, and the catalytic function of P450 4F proteins heterologously expressed in E. coli was estimated by analyzing leukotriene B 4 20-hydroxylation and ebastine hydroxylation.…”
Section: Discussionmentioning
confidence: 95%
“…In a previous study, de novo gene expression analysis in marmosets indicated expression of the marmoset P450 4F11-like gene in the liver and the 4F12-like gene in the liver, small intestine, and kidney (Shimizu et al, 2014): however, marmoset P450 4F forms have not been identified and characterized. In this study, we identified four novel P450 4F genes using the marmoset genome data, including P450 4F2, 4F3, 4F11, and 4F12, and the catalytic function of P450 4F proteins heterologously expressed in E. coli was estimated by analyzing leukotriene B 4 20-hydroxylation and ebastine hydroxylation.…”
Section: Discussionmentioning
confidence: 95%
“…However, P450s, which are major drug metabolizing enzymes, have not been fully identified and analyzed in marmosets. In a previous study, the tissue-specific expression patterns of P450 1-3-like genes were shown (Shimizu et al, 2014). In this study, we newly cloned P450 1A1 and 1B1 cDNAs from marmoset livers by RT-PCR using the genespecific primers designed based on the marmoset genome sequences.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Shimizu et al (2014) and Uehara et al (2015a,b,c,d) identified marmoset P450 2A, 2C, 2D, and 3A genes and characterized enzymatic properties of these proteins. Most marmoset P450s have high sequence identities (.85%) to the homologous human P450s at the amino acid level.…”
Section: Introductionmentioning
confidence: 99%
“…One of the New World Monkeys, the common marmoset (Callithrix jacchus), is used in various research fields such as drug metabolism because of advantageous features including their small body size (Sasaki, 2015). Gene expression of marmoset P450 1A, 2A, 2B, 2C, 2D, 2E, 2J, and 3A in livers was reported (Shimizu et al, 2014), but genetic polymorphisms in marmoset drug metabolism have not been investigated thus far.…”
Section: Introductionmentioning
confidence: 99%